Bioproduction of highly charged designer peptide surfactants via a chemically cleavable coiled‐coil heteroconcatemer. Issue 2 (10th October 2014) - Fletcher, Nicholas L.; Paquet, Nicolas; Dickinson, Ellyce L.; Dexter, Annette F.
ABSTRACT Designer peptides have recently attracted attention as self‐assembling fibrils, hydrogelators and green surfactants with the potential for sustainable bioproduction. Carboxylate‐rich peptides in particular have shown potential as salt‐resistant emulsifiers; however the expression of highly charged peptides of this kind remains a challenge. To achieve expression of a strongly anionic helical surfactant peptide, we paired the peptide with a cationic helical partner in a coiled‐coil miniprotein and optimized the polypeptide sequence for net charge, hydropathy and predicted protease resistance (via the Guruprasad instability index). Our design permitted expression of a soluble concatemer that accumulates to high levels (22% of total protein) in E. coli. The concatemer showed high stability to heat and proteases, allowing isolation by simple heat and pH precipitation steps that yield concatemer at 133 mg per gram of dry cell weight and >99% purity. Aspartate‐proline sites were included in the concatemer to allow cleavage with heat and acid to give monomeric peptides. We characterized the acid cleavage pathway of the concatemer by coupled liquid chromatography‐mass spectrometry and modeled the kinetic pathways involved. The outcome represents the first detailed kinetic characterization of protein cleavage at aspartate‐proline sites, and reveals unexpected cleavage preferences, such as favored cleavage at the C‐termini of peptide helices. Chemical denaturation of the concatemer showed an extremely high thermodynamic stability of 38.9 kcal mol−1, with cleavage decreasing the stability of the coiled coil to 32.8 kcal mol−1. We determined an interfacial pressure of 29 mN m−1 for both intact and cleaved concatemer at the air‐water interface, although adsorption was slightly more rapid for the cleaved peptides. The cleaved peptides could be used to prepare heat‐stable emulsions with droplet sizes in the nanometer range. Biotechnol. Bioeng. 2015;112: 242–251. © 2014 Wiley Periodicals, Inc.